Outbreak of human brucellosis in Southern Brazil and historical review of data from 2009 to 2018. - Tamilly Silva Lemos; Juliana Clelia Cequinel; Tania Portela Costa; Amanda Boni Navarro; Andressa Sprada; Flávia Kazumi Shibata; Regina Gondolfo; Felipe Francisco Tuon (Public Library of Science (PLoS), 2018)
BACKGROUND:Human brucellosis (HB) is a bacterial zoonosis that is more frequent in low income and middle-income countries; it is sometimes associated with outbreaks. The aim of this study was to describe the largest outbreak of HB in Brazil. METHODS:A retrospective cohort study of patients suspected of having contracted HB in the state of Paraná, Southern Brazil from January 2009 to January 2017. Following an outbreak of 51 cases of HB in a slaughterhouse at Paiçandu in 2014, HB was defined as an obligatory reportable disease in the State. Diagnostic tests for HB included serum agglutination, ELISA (IgG or IgM) and polymerase chain reaction (PCR). Clinical, laboratorial and epidemiological data were analyzed. A P value of 0.05 was considered statistically significant. RESULTS:Out of a total of 3,941 patients, 754 presented with a positive test result for HB. After 2014, there was a significant increase in the number of cases, exceeding 100 cases per trimester. In the beginning of 2015, the workgroup of HB started several actions for prevention and treatment, and the number of cases progressively diminished to fewer than 20 cases per trimester. Of 191 reported cases, an occupational risk was found in 84.7%; most cases occurred in farmers (60.0%), veterinarians (17.6%) and slaughterhouse workers (14.7%). Manipulation of animals and unpasteurized milk consumption were associated with positive Brucella IgM ELISA with an odds ratio (OR) of 1.42 (1.09-1.84) and 1.48 (1.01-2.15), respectively. CONCLUSIONS:HB outbreaks can occur in low to middle-income countries and are associated with slaughterhouse work, handling of unpasteurized milk and animal manipulation. Intensive programs for control of HB are important to reduce the number of cases.